Energy and protein content of Tedera (Bituminaria bituminosa) - Ventura M.R.; Méndez P.; Flores M.P.; Rodríguez R.; Castañón J.I.R. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Nutrient content was determined in tree subspecies of Bituminaria bituminosa (also called Psoralea bituminosa): crassiuscula, albormaginata and bituminosa collected in Canary Islands in autumn, spring, winter and summer. Crude protein content ranged 15-20 per cent and NDF content ranged 41-56 per cent. In vitro OM digestibility ranged 55-65 per cent. Based on digestible OM content of subspecies, estimated net energy content ranged 4.6-5.3 MJ per kg DM, with not significant differences among subspecies neither season.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)